2012
DOI: 10.1007/s00402-012-1519-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin sealants in orthopaedic surgery: practical experiences derived from use of QUIXIL® in total knee arthroplasty

Abstract: Regarding cost effectiveness and benefit no indication for the use of 2 ml QUIXIL(®) fibrin sealant in standard knee arthroplasty could be proofed statistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…The studies measure external blood loss as the volume contained in the drain, total blood loss, or a combination of both. Six studies [16,18,19,21-23] (369 patients) reported postoperative drainage. Postoperative time until the evaluation of the drainage was different in each trial: 12 h for the study by Wang et al, 24 h for the study by Skovgaard et al, 72 h in the studies by Notarnicola et al and Sabatini et al, and no time given in the study by Levy et al The general appraisal of the postoperative drainage indicated that the use of fibrin sealant significantly reduced postoperative drainage (WMD −346, 95% CI −496.29 to −197.54, P  < 0.00001, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies measure external blood loss as the volume contained in the drain, total blood loss, or a combination of both. Six studies [16,18,19,21-23] (369 patients) reported postoperative drainage. Postoperative time until the evaluation of the drainage was different in each trial: 12 h for the study by Wang et al, 24 h for the study by Skovgaard et al, 72 h in the studies by Notarnicola et al and Sabatini et al, and no time given in the study by Levy et al The general appraisal of the postoperative drainage indicated that the use of fibrin sealant significantly reduced postoperative drainage (WMD −346, 95% CI −496.29 to −197.54, P  < 0.00001, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [19,21] (144 patients) were used to perform the meta-analysis with the range of motion. Postoperative time to evaluate treatment was 8 days for the Kluba et al study and 17 days for the Notarnicola et al study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two techniques-simple stitch (two loops in parallel) and the figure-of-eight stitch-are widely used in clinical practice for suturing soft tissues (Hansen et al, 2011;Kluba et al, 2012;Miozzari et al, 2010;Oinuma et al, 2014). The last suturing technique involves the use of a novel stitch, hereinafter referred to as double loop (DL) stitch.…”
Section: Suturing Techniquesmentioning
confidence: 99%
“…TXA is an antifibrinolytic that binds to specific sites of both plasminogen and plasmin, competitively inhibiting the activation of plasminogen to plasmin and thus inhibiting dissolution of clots. Opinions are mixed over the true efficacy of FS in reducing perioperative blood loss and reducing the need for blood transfusion (10)(11)(12)(13)(14)(15)(16). In contrast, multiple trials have clearly demonstrated that TXA is highly reliable (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%